1987
DOI: 10.1123/ssj.4.3.229
|View full text |Cite
|
Sign up to set email alerts
|

Size of Community of Origin and Recruitment to Professional and Olympic Hockey in North America

Abstract: A conventional wisdom in the lay sociology of sport journalism is that North American professional ice hockey players are disproportionately recruited from smaller communities and rural areas. One explanation given for this is that avenues for social mobility are more limited in such communities and that sport is heavily pursued as one of the few areas of opportunity. Sections of the sociological literature would suggest, though, that the opposite relationship may occur because larger cities have better opport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
1
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 4 publications
4
59
1
7
Order By: Relevance
“…The 1976 Canadian census characterizes populated areas of less than 1000 as lacking the infrastructures that are usually common to a city, which may result in fewer opportunities to invest in physical activities and sports. The lack of facilities and playing partners, typical in small rural areas, appears to be detrimental to the early development of sport skills (Curtis & Birch, 1987). This minimum populated areas effect was not seen in the US data and may be due to the 1980 US census not providing the number of people living in rural areas in the USA.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…The 1976 Canadian census characterizes populated areas of less than 1000 as lacking the infrastructures that are usually common to a city, which may result in fewer opportunities to invest in physical activities and sports. The lack of facilities and playing partners, typical in small rural areas, appears to be detrimental to the early development of sport skills (Curtis & Birch, 1987). This minimum populated areas effect was not seen in the US data and may be due to the 1980 US census not providing the number of people living in rural areas in the USA.…”
Section: Discussionmentioning
confidence: 63%
“…The remaining values in each of the census subdivisions of population yielded values that closely resembled the expected proportions. Based on these findings, Curtis and Birch (1987) suggested that ''top players are more likely to come from communities large enough to build rinks, but not so large that the demand for ice time outweighs opportunities to skate'' (p. 239). Unfortunately, the qualitative nature of Carlson's (1988) study and the focus of Curtis and Birch's (1987) study on ice hockey did not permit the identification of optimal city sizes for sport development across different sports and different sport systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…De acordo com algumas pesquisas, a falta de infraestrutura destas pequenas cidades pode resultar em baixos investimentos públicos e privados de incentivo à prática esportiva e, consequentemente, poucas oportunidades de vivência prática do esporte e de orientação qualificada (CÔTÉ et al, 2006). Além disto, a escassez de estrutura física e a falta de crianças/amigos para a prática do futebol são fatores que podem inibir outras facilidades encontradas nas pequenas cidades, como a prática por longo período de tempo e o desenvolvimento de habilidades específicas de jogo (CURTIS;BIRCH, 1987 No contexto do Futebol Brasileiro, a origem desta disparidade de concentração de jogadores pelos meses do ano pode estar associada ao processo de identificação de jogadores nas categorias de base e aos métodos de avaliação de trabalho dos profissionais (treinadores, preparadores físicos, auxiliares técnicos, entre outros) que lidam diretamente com os jovens jogadores. A pressão exagerada por vitórias e conquistas nas etapas de formação, pode ter reflexos diretos no processo de identificação de talentos que, consequentemente, irá influenciar o processo de formação e seleção do jogador até o mais alto nível de rendimento (DIAZ DEL CAMPO et al, 2010).…”
Section: O íNdice De Desenvolvimento Humano E a Data De Nascimento Pounclassified